6 - Organizações da Sociedade Civil em Moçambique: sustentabilidade, dependência, imposição - Ernesto Nhatsumbo,; Luca Bussotti, (Africa Development, 2025)
Mozambican civil society has experienced a not always linear evolution, since it began to strengthen itself in the early 1990s. The dependence, not only financially, but also programmatically and managerially of most such organizations, squeezed between government pressure and the demands of international donors, has been the hallmark. The result was that only a few organizations were able to evolve, having their own agenda, competent staff and constant funds that would allow medium- and long-term programming of their actions with local communities. In most cases, national civil society organizations remained weak, with a clear skills deficit and therefore dependent on donors, usually international ones. This article seeks to report research that was carried out in Mozambique with three main subjects: international donors, national NGOs and other national entities like foundations, that serve as collectors of donor funds, and grassroots organizations, which represent the ultimate beneficiaries of the funds. Through a qualitative approach, based essentially on interviews with key informants, the result was that the tripartite mechanism implemented in Mozambique is limited, fostering the dependence of civil society organizations rather than inducing them to change and evolve towards greater quality and stability, not only of a financial kind.